2022
DOI: 10.3389/fimmu.2022.955841
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease PRSS23 drives gastric cancer by enhancing tumor associated macrophage infiltration via FGF2

Abstract: Serine proteases has been considered to be closely associated with the inflammatory response and tumor progression. As a novel serine protease, the biological function of PRSS23 is rarely studied in cancers. In this study, the prognostic significance of PRSS23 was analyzed in two-independent gastric cancer (GC) cohorts. PRSS23 overexpression was clinically correlated with poor prognosis and macrophage infiltration of GC patients. Loss-of-function study verified that PRSS23 plays oncogenic role in GC. RNA-seq, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…6B ). Previous studies have reported that FGF2 plays critical roles in macrophage infiltration and polarization [ 22 , 27 31 ]. Thus, we analyzed the correlation between IGFBP7 expression and immune infiltration using two methods, including CIBERSORT and TIMER.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6B ). Previous studies have reported that FGF2 plays critical roles in macrophage infiltration and polarization [ 22 , 27 31 ]. Thus, we analyzed the correlation between IGFBP7 expression and immune infiltration using two methods, including CIBERSORT and TIMER.…”
Section: Resultsmentioning
confidence: 99%
“…Takase et al reported that FGF2 promotes TAM infiltration and tumor progression in esophageal squamous cell carcinomas through FGF2/FGFR1 axis [ 21 ]. Similarly, Qin and colleagues found that serine protease PRSS23 promotes GC progression by positively regulating FGF2 secretion to enhance TAM infiltration [ 22 ]. In this study, we identified a novel role of IGFBP7 in regulating TAM infiltration by enhancing FGF2 secretion and activating FGF2/FGFR1/PI3K/AKT signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The western blotting assay was performed as previously described ( 46 ). After 72h transfected with miRNA, GIC cells were lysed in RIPA buffer added 1 mM PMSF.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was performed with default method in Seurat package. As we previously described [56][57][58][59], the P values for gene expression analysis in different groups were estimated using Wilcoxon Rank Sum test. As for cell communication analysis, statistical analysis was also performed with default method in CellChat package, and default method of "triMean" was used for computing the average gene expression per cell group.…”
Section: Statisticsmentioning
confidence: 99%